Self‐consistent simulation of two‐dimensional electron gas characteristics of a novel (InxAl1–xN/AlN) MQWs/InN/GaN heterostructure. Issue 5 (3rd February 2016) - Li, Wei; Wang, Quan; Wang, Cuimei; Yin, Haibo; Yan, Junda; Gong, Jiamin; Li, Baiquan; Wang, Xiaoliang; Wang, Zhanguo
Abstract : In this paper, (In x Al1– x N/AlN) MQWs/InN/GaN heterostructure with a (In x Al1– x N/AlN) MQWs barrier layer and an InN channel layer is presented. The numerical calculations of 2DEG characteristics are made using a self‐consistent solution of the Schrödinger and Poisson equations. The influence of (In x Al1– x N/AlN) MQWs and InN layer on band diagrams, 2DEG sheet density and carrier confinement are studied. The results show that an InN insert layer can improve the carrier‐confinement ability without degrading the 2DEG sheet density in the heterostructure. The (In x Al1– x N/AlN) MQWs/InN/GaN heterostructure has both a larger 2DEG sheet density and better confinement of 2DEG than conventional InAlN/GaN and AlGaN/GaN heterojunctions. The 2DEG sheet density is as dramatically large as 3.85 × 10 13 cm −2 with an AlN thickness of 1.5 nm, an In0.18 Al0.82 N thickness of 1.5 nm, an InN thickness of 0.5 nm, and pair number of 5. In addition, the influence of AlN thickness, InAlN thickness, indium content, and pair number on the 2DEG sheet density of the (In x Al1– x N/AlN) MQWs/InN/GaN heterostructure has been studied.